Banking on Seniority: The IMF and the Sovereign's Creditors. Issue 2 (21st July 2014) - Erce, Aitor
<x xml:space="preserve">Abstract</x> The programs designed by the International Monetary Fund (IMF) during the Global Financial Crisis have shown more awareness of the importance of domestic demand for the prospects of economic recovery. Yet the IMF has continued to do little about the late payments made by governments to domestic creditors and suppliers. In contrast, the greater protection historically awarded by the IMF to foreign creditors has endured throughout the recent crisis. The article suggests that, in order to adequately balance foreign creditor seniority and growth objectives, the IMF may sometimes need to emphasize equitable burden‐sharing across categories of creditors rather than privilege the interests of international bond markets.